Alexander Pereira all out of passion (Langbein & Partner, 2012)
A film portrait of the artistic director of the famous Salzburger Festspiele, Alexander Pereira. For this documentary, Pereira allows an insight into his private life as well as his work as an experienced manager and opera singer. Unexpectedly open he lets young filmmaker Florian Gebauer accompany him to India, where his father, a former Austrian ambassador was killed in an air crash when he was only two years old. India is also the place where he, together with his good friend Zubin Mehta, has established an orphanate that he enjoys visiting regularly. Back at his apartment in Switzerland the enthusiastic hobby-cook and his partner invite their friends like Thomas Hampson to a "Wiener Schnitzel" dinner and let the filmmaker being part of his private activities. In an interview, the charismatic 58-year-old starts talking about music, his passion, and his eyes light up. Originally he wanted to be a singer, and singing still is one of his hobbies. The image of his personality, his preferences, strengths and weaknesses get complemented in interviews with his friends and companions like Nikolaus Harnoncourt, Zubin Metha, Eric Bechtolf and his partner Daniela Weisser de Sosa